Stable Seamless Interfaces and Rapid Ionic Conductivity of Ca–CeO2/LiTFSI/PEO Composite Electrolyte for High‐Rate and High‐Voltage All‐Solid‐State Battery - Chen, Hao; Adekoya, David; Hencz, Luke; Ma, Jun; Chen, Su; Yan, Cheng; Zhao, Huijun; Cui, Guanglei; Zhang, Shanqing (Advanced energy materials, 2020)
Stable and seamless interfaces among solid components in all‐solid‐state batteries (ASSBs) are crucial for high ionic conductivity and high rate performance. This can be achieved by the combination of functional inorganic material and flexible polymer solid electrolyte. In this work, a flexible all‐solid‐state composite electrolyte is synthesized based on oxygen‐vacancy‐rich Ca‐doped CeO2 (Ca–CeO2) nanotube, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and poly(ethylene oxide) (PEO), namely Ca–CeO2/LiTFSI/PEO. Ca–CeO2 nanotubes play a key role in enhancing the ionic conductivity and mechanical strength while the PEO offers flexibility and assures the stable seamless contact between the solid electrolyte and the electrodes in ASSBs. The as‐prepared electrolyte exhibits high ionic conductivity of 1.3 × 10−4 S cm−1 at 60 °C, a high lithium ion transference number of 0.453, and high‐voltage stability. More importantly, various electrochemical characterizations and density functional theory (DFT) calculations reveal that Ca–CeO2 helps dissociate LiTFSI, produce free Li ions, and therefore enhance ionic conductivity. The ASSBs based on the as‐prepared Ca–CeO2/LiTFSI/PEO composite electrolyte deliver high‐rate capability and high‐voltage stability. Ca‐doped CeO2 nanotubes with rich oxygen vacancies provide abundant interaction sites for stable and seamless contact with flexible polyethylene oxide (PEO) and afford enhanced ionic conductivity (1.3 × 10−4 S cm−1 at 60 °C) and increased transference number of 0.453 with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt. The all‐solid‐state batteries based on the as‐prepared (Ca–CeO2/PEO/LiTFSI) electrolyte deliver superior rate capability, excellent long‐term cycling, and high‐voltage stability.